ASP.NET 4 Unleashed - Walther, Stephen; Hoffman, Kevin; Dudek, Nate (Sams, 2010)
The most comprehensive book on Microsoft's new ASP.NET 4, ASP.NET 4 Unleashed covers all facets of ASP.NET development. Led by Microsoft ASP.NET program manager Stephen Walther, an expert author team thoroughly covers the entire platform. The authors first introduce the ASP.NET Framework's basic controls and show how to create common site-wide layouts and styles. Next, they cover all aspects of accessing, presenting, organizing, and editing data. You'll find thorough and practical sections on building custom components and controls, providing effective site navigation, securing sites and applications, and much more. This book presents hundreds of realistic code examples, reflecting the authors' unsurpassed experience with ASP.NET both inside and outside Microsoft. Build interactive Web Forms, validate form data, and upload files Provide interactive calendars, wizards, site maps, and other valuable features Design efficient, maintainable sites with Master Pages and Themes Build data-driven applications with database controls, ADO.NET data access components, QueryExtender, LINQ to SQL, and WCF Data Services Generate charts on the fly with the new Chart Control Extend ASP.NET with custom controls and reusable components Create site registration and authentication systems that store membership data in SQL Server or Active Directory Use URL Routing to build dynamism, flexibility, readability, and SEO-friendliness into your URLs Improve performance and scalability with caching and preloading Maintain state with cookies, cookieless session state, and profiles Localize, configure, package, and deploy ASP.NET applications Use the ASP.NET MVC Framework to improve agility, testability, speed to market, and extensibility Retrofit existing ASP.NET applications with Ajax and build pure client-side Ajax web applications Construct a complete ASP.NET 4 website from start to finish.